Dari Radio Ke Instagram Kunci PRFM Bertahan di Era Digital - Herawati, Nia; Anggraini, Clara Novita (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
In today's digital era, not many radio stations survive. Social media has become an influential communication tool for building images and relationships with audiences. PRFM (Pikiran Rakyat FM) News is a radio station that still survives today and keeps up with the times. The purpose of this research is to find out how PRFM (Pikiran Rakyat FM) News Instagram communication is planned. In an effort to understand the strategies used, this research applies a qualitative approach with descriptive methods because it allows researchers to gain in-depth insight into how PRFM News operates in conveying information to the audience. The results of this research show that PRFM follows ongoing trends. In this way, this PRFM communication strategy can maintain relevance and attract public interest in communicating every problem. PRFM also highlights the focus on message-composing techniques on Instagram. This shows awareness of the importance of effective message presentation to attract attention and retain the audience